MnO2/Carbon Composites for Supercapacitor: Synthesis and Electrochemical Performance - Wu, Dan; Xie, Xiubo; Zhang, Yuping; Zhang, Dongmei; Du, Wei; Zhang, Xiaoyu; Wang, Bing (Frontiers in Materials, 2020)
As an emerging energy storage device, the supercapacitor with high energy density, fast charging/discharging, and good cycle stability has aroused great interest. The performance of supercapacitors mainly depend on the electrode material. Manganese dioxide (MnO2) has emerged as one of the most promising electrode materials for high theoretical specific capacitance, wide potential range, high electrochemical activity, and environmental friendliness. However, its deteriorated volume expansion and inherently low conductivity limit its development and application in supercapacitors. To circumvent the mentioned issues, the porous, thin film, or layered composite materials were prepared to enhance the electrical conductivity and specific surface area of MnO2. Carbon materials are the ideal choice to compound with MnO2 owing to their low electrical resistance, significant thermal stability, large specific surface area, and porosity. Up to now, several kinds of MnO2/carbon composites as supercapacitor electrodes have been designed and fabricated. Herein, we give a concise review of the latest researches on MnO2/carbon supercapacitor electrodes, focusing on the fabrication strategies and analyzing the influencing factors of electrochemical performance of MnO2/carbon materials. An outlook on the possible development directions in future of designing high-performance MnO2/carbon materials for the current challenges is also provided.